Biota turnovers from phylogenies. Issue 12 (December 2017) - Quental, Tiago
Phylogenetic data infer temporal clustering of immigration and re-diversification of Australian lizards and snakes, suggesting that climatic and geological changes may have precipitated re-assemblies of this vertebrate group.